Economic Burden of Herpes Zoster and Post-Herpetic Neuralgia in Adults 60 Years of Age or Older: Results from a Prospective, Physician Practice-Based Cohort Study in Kushiro, Japan - Nakamura, Hiroyuki (Drugs Real World Outcomes, 2017)
BACKGROUND AND OBJECTIVE: Herpes zoster has a high incidence rate among people aged ≥ 60 years and can lead to serious complications such as post-herpetic neuralgia. There are currently no data on the economic burden of herpes zoster and post-herpetic neuralgia in Japan, and the objective of this study was to address this gap. METHODS: A total of 412 patients aged ≥ 60 years diagnosed with herpes zoster were recruited. Demographic, clinical, and healthcare resource utilization data on patients with herpes zoster or post-herpetic neuralgia collected via case report forms were used to estimate direct medical cost. Data obtained from a questionnaire survey among patients with herpes zoster/post-herpetic neuralgia were used to estimate transportation cost and productivity loss. RESULTS: The mean number of outpatient visits was 5.7. Prescription medications were the main cost driver accounting for 60% of the direct medical cost. The mean direct medical and total herpes zoster-related costs per patient were ¥43,925 and ¥57,112, respectively, and were higher in patients with post-herpetic neuralgia than in those with herpes zoster without complications. Direct medical cost represented 77%, productivity loss 19%, and transportation cost 4% of the total. CONCLUSIONS: This is the first study of the economic burden of herpes zoster and post-herpetic neuralgia in Japan and it demonstrated substantial direct medical cost as a result of the multiple outpatient visits and prescription medications required. These findings provide baseline data for possible future economic evaluations of new herpes zoster/post-herpetic neuralgia interventions. TRIAL REGISTRATION: This cost analysis is part of a prospective, physician practice-based cohort study conducted between June 2013 and February 2015 in Kushiro, Japan (Clinicaltrials.gov identifier NCT01873365, registered on 6 June, 2013).